Self-concept Characteristics and Self-Perceptions Accuracy of Children with Attention Deficit Disorder with Hyperactivity of Buenos Aires. - María Fernanda Molina; Ana Laura Maglio (CAEN, 2013)
The aim of this paper was to study the characteristics of the self-concept of children with ADHD in the Área Metropolitana Bonaerense (AMBA, Argentine) and the accuracy in their self-perceptions. Participants were 100 boys and girls aged 7 to 13 years and one of their parents. Children formed three groups: children diagnosed as ADHD (DSM IV criteria), children who assist to psycho- therapy but did not meet diagnostic criteria for ADHD and normally developed children. Children completed the Self-Perception Profile for Children (SPPC). Parents answered the Parent's Rating Scale of Child's Actual Behavior (PRS). It was found that children with psychological problems (ADHD or other issues for psychotherapeutic assistance) had more negative self-perception than those who had no difficulties. The self-perceptions of children with ADHD do not differed from those of children with other impairment. Children with ADHD showed greater positive bias in their self-perception than the other groups of children.